Topography optimization of an enclosure panel for low-frequency noise and vibration reduction using the equivalent radiated power approach. (5th December 2019) - Kim, Hyun-Guk; Nerse, Can; Wang, Semyung
Abstract: An enclosure panel is widely used in industrial applications. The panel under a dynamic loading excites the surrounding air medium and noise is radiated into the acoustic space. The radiated sound can be suppressed by having changes in the structure. The noise reduction performance can be further improved by a design optimization. In this study, a topography optimization is conducted to design an enclosure panel. Topography optimization results in a bead pattern, which helps maintain the thickness at a constant level throughout the structure. The final optimized structure can be manufactured using a stamping process. Compared with other optimization methods, topography optimization requires minimal manufacturing effort and cost, with no additional increase in mass. Moreover, this type of optimization is effective for noise reduction problems because no holes are created in the structure. In this study, the objective function selected to minimize the low-frequency noise is the equivalent radiated power. The topography optimization of the enclosure panel has been conducted using the commercial software Altair OptiStruct, with loads and constraints considered. In order to verify the optimization result, in-situ experiment was performed with panels produced by the stamping process. Graphical abstract: Unlabelled Image Highlights: Low-frequency noise is reduced by a design optimization of enclosed panel. Topography optimization process is implemented using Altair OptiStruct. The performance of noise and vibration of the enclosed panel is verified with in-situ experiment.